Molecular identification of Antarctic canola oil-degrading bacteria - Mohd Zahri, Khadijah Nabilah; Sabri, Suriana; Gomez-Fuentes, Claudio; Abdul Khalil, Khalilah; Convey, Peter; Zulkharnain, Azham; Ahmad, Siti Aqlima (Polska Akademia Nauk, 2025)
The detrimental impacts of human activity in Antarctica can pose significant threats to the continent’s ecosystems and diversity. Various pollutants have been detected in Antarctica, including hydrocarbon compounds derived from oils. The widespread use of canola oil in catering at Antarctic research stations raises the possibility of its release into the environment, either through accidental spillage or via waste cooking oil present in grey water. To help address this issue, a bacterial consortium (reference BS14) obtained from the natural Antarctic environment was isolated and confirmed to be capable of breaking down canola oil. The identity of members of the consortium was investigated using metagenomic analysis, with lipase-producing bacteria further examined using Sanger sequencing. The consortium in media not exposed to canola oil consisted primarily of Proteobacteria and Firmicutes in almost equal percentages. After being exposed to either fresh or waste canola oil, high proportions of representatives of Pseudomonadaceae and Carnobacteriaceae were present. Amongst the bacterial taxa identified in the metagenomic analysis, representatives of the genera Pseudomonas and Carnobacterium were confirmed to be responsible for biodegrading waste canola oil and pure canola oil. This study offers novel insights into the potential of bacterial consortia for canola oil bioremediation in Antarctica.